DGA–Duval Triangle Analysis for Early Thermal Fault Diagnosis of Transformer Oil - Muhtar, Ali; Azizah Umar, Ismi (Universitas Muhammadiyah Surakarta, 2025)
This study assesses the health of the T5 transformer oil at the Geothermal Power Plant to enable early thermal-fault diagnosis and support evidence-based maintenance. Methods comprised Dissolved Gas Analysis (DGA) with TDCG evaluation per IEEE C57.104-2019, Duval Triangle mapping, and breakdown-voltage (BV) and water-content testing per IEEE C57.106-2015. Results show TDCG of 686 ppm (Condition 1) with CO₂ at 10,000 ppm; gas fractions CH₄ 70.18%, C₂H₄ 29.24%, and C₂H₂ 0.58% place the point in zone T2 (300–700 °C). Water content is 29 ppm—above the recommended limit for transformers <72.5 kV (good: <10 ppm)—while mean BV is 73.4 kV, exceeding the 40 kV minimum. The evidence indicates a medium-level thermal fault with high moisture contamination. Oil filtering/dehydration and periodic DGA trend monitoring are recommended to mitigate failure risk and inform data-driven maintenance planning